Characterization and production of statistics on micro and small companies of region Huánuco - Marín Mozombite, Manuel (2009)
In the present work it is tried to characterize a the MYPES of Huánuco taking care of: the activities that they develop, the added value that undergoes the insumos and products in himself within the production systems or number of workers. For it it was counted on information provided by the SUNAT, the Regional address of Production, and Provincial and distritales Municipalities; as well as the successfully obtained one by means of a questionnaire, applied to a oriented size of sample. The systematization of such information gives to know that in the department of Huánuco: at the moment 44 029 companies exist, that make 217 activities; 95,8% of registered companies belong to the tertiary sector; in the province of Huánuco the greater enterprise activity or by the number of existing companies (30 845 of a departmental total of 44 029) or by the number of activities is concentrated to that these companies are dedicated (208 of a total of 217); in the province of Huacaybamba the smaller enterprise activity exists: 125 companies that are dedicated to 29 activities; thje accord the number of workers midde for enterprise, the enterprises of development of Huánuco are micro companies.